Substitution of perioperative albumin deficiency disorders (SuperAdd) in adults undergoing vascular, abdominal, trauma, or orthopedic surgery: protocol for a randomized controlled trial - Stefan J. Schaller; Kristina Fuest; Bernhard Ulm; Sebastian Schmid; Catherina Bubb; Rüdiger von Eisenhart-Rothe; Helmut Friess; Chlodwig Kirchhoff; Thomas Stadlbauer; Peter Luppa; Manfred Blobner; Bettina Jungwirth (Trials, 2020)
Abstract Background Hypalbuminemia is associated with numerous postoperative complications, so a perioperative albumin substitution is often considered. The objective of SuperAdd is to investigate whether substitution of human albumin, aiming to maintain a serum concentration > 30 g/l, can reduce postoperative complications in normovolemic surgical patients in comparison with standard care. Methods/design SuperAdd is a single-center, prospective, randomized, outcome-assessor blinded, patient blinded controlled trial. The primary outcome is the frequency of postoperative complications identified using the Postoperative Morbidity Survey graded ≥ 2 according to the Clavien-Dindo Score. Adult patients at risk to develop hypalbuminemia, i.e., ASA III or IV or high-risk surgery, are recruited after written informed consent was obtained. The albumin concentration is assessed before the induction of anesthesia and every 3 h until admission to the postanesthesia care unit. If albumin concentrations drop below 30 g/l, patients are randomly allocated to the control or the treatment group. The study intervention is a goal-directed human albumin substitution aimed at a concentration > 30 g/l during surgery and postanesthesia care unit stay. The patients in the control group are treated according to standard clinical care. Postoperative visits are to be performed on days 1, 3, 5, 8, and 15, as well as by telephone 6 months after surgery. Discussion SuperAdd is the first clinical trial in a surgical population investigating the effect of a goal-directed albumin substitution aiming at a serum level > 30 g/l. The nonrestrictive selection of patients guarantees that the patients without albumin screening will most likely not develop hypalbuminemia, thus ensuring generalizability of the study results. Trial registration EudraCT 2016-001313-24. Registered on 5 September 2016. Clinical Trials NCT03167645. Registered on 18 October 2016 and has the Universal Trial Number (UTN) U1111-1181-2625.